2020
DOI: 10.3389/fpsyg.2020.01090
|View full text |Cite
|
Sign up to set email alerts
|

A Process Evaluation of a Performance Psychology Intervention for Transitioning Elite and Elite Musicians

Abstract: The present study presents a process evaluation of a performance psychology intervention for transitioning elite and elite musicians. The goal of the intervention was to provide participants with an amalgamation of evidence-informed principles, aimed to improve their quality of practice and performance preparation. The intervention consisted of an educational session followed by four workshops. In total, eight transitioning elite and seven elite musicians participated. Process measures included quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…Such strategies also relate to the principle of planned disruptions , which might increase individuals’ resilience to pressure (Kegelaers et al, 2020). As such, future research might further examine how planned disruptions can be used to prepare for high-pressure musical performances (see also Kegelaers & Oudejans, 2020). Finally, substance use was mentioned as a performance management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies also relate to the principle of planned disruptions , which might increase individuals’ resilience to pressure (Kegelaers et al, 2020). As such, future research might further examine how planned disruptions can be used to prepare for high-pressure musical performances (see also Kegelaers & Oudejans, 2020). Finally, substance use was mentioned as a performance management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This is at odds with previous studies on choking under pressure in sports (Gröpel & Mesagno, 2019; Mesagno & Beckmann, 2017) and indicates that transferring sport-specific methods to music need not automatically bring the same benefits. It is likely that the interventions must be adjusted to the field of music before they can show performance-facilitating effects (Kegelaers & Oudejans, 2020). For example, the duration of left-hand dynamic handgrip could be shortened, or the intervention could be applied to musicians playing other instruments than violin and viola, as several participants in the dynamic handgrip group reported that the handgrip resulted in a stiff left hand and in turn affected their playing ability.…”
Section: Discussionmentioning
confidence: 99%
“…The less positive evaluation of the dynamic handgrip may be due to its unclear association with music. Whereas PPRs and goal-setting can be directly linked to music-related thoughts and behavior, such as when a PPR element involves music-relevant cues (Kinne, 2016; Osborne et al, 2014) or goal-setting is used to better structure music practice (Burwell & Shipton, 2013; Kegelaers & Oudejans, 2020), the dynamic handgrip does not focus on any music-related element and may thus appear less intuitive to musicians. Therefore, from an applied perspective, it seems essential to educate and convince musicians of the handgrip intervention mechanism and benefits when the musicians attempt to use it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance anxiety presents a substantial challenge to musicians' achievement of optimal performance, health, and well-being in educational and professional settings (Kenny & Ackermann, 2016;Osborne & McPherson, 2019). Evidence of psychological distress and compromised educational outcomes for music students in university settings International Journal on Innovations in Online Education 4(2) 2020 2377-9527/20/$35.00 © 2020 by Begell House, Inc. www.begellhouse.com (Ginsborg et al, 2012) has prompted pedagogues to introduce performance psychology teaching into conservatory curricula with promising results in traditional face-to-face (F2F) formats (Kegelaers & Oudejans, 2020;Osborne et al, 2014;Spahn et al, 2016). As the practice of blended and fully online teaching expands, studies have begun to emerge that explore methods and student perceptions toward teaching online.…”
Section: Introductionmentioning
confidence: 99%